Atomic-scale investigation on the interface structure of {22‾01} α2-Ti3Al deformation twins in polysynthetically twinned TiAl single crystals. (January 2021) - He, Neng; Qi, Zhixiang; Cheng, Yongxin; Zhang, Jinpeng; Lianlong He; Chen, Guang
Abstract: The interface structure of {2 2 ‾ 01} α2 -Ti3 Al deformation twins formed during tensile deformation of polysynthetically twinned (PST) TiAl single crystals at 900 °C has been studied systematically by aberration-corrected scanning transmission electron microscopy. Numerous superlattice intrinsic stacking faults (SISFs) are formed on the (0001) basal plane of α2 twins, thereby resulting in the formation of steps on the twin boundaries. The height of steps equals to the spacing of the (2 2 ‾ 01) twinning plane. The basal-plane SISFs formed in α2 twins can't be attributed to the glide of Shockley superpartial dislocations. Lattice correspondence analyses based on classical twinning theory reveal that complex atomic shuffle and interchange shuffling are responsible for the formation of twinning and basal-plane SISFs in α2 twins. In addition, basal-plane antiphase boundaries (APB) are formed at the vicinity of α2 twin tips to relieve the stress concentration imposed by misfit dislocations. Highlights: { 2 2 ‾ 01 } α2 deformation twin occurs in PST Ti-45Al-8Nb single crystals with 0° lamellar orientation after tension at 900 °C. Abundant I1 type basal-plane SISFs connected with steps exist inside α2 twins. Basal-plane APB are formed at the vicinity of α2 twin tips to relieve the stress concentration imposed by misfit dislocations. The mechanism of twinning in α2 can be explained by the method of lattice correspondence.